The use of UGM’s eLOK as a Student Learning Outcomes Evaluation Platform - Marvianto, Ramadhan Dwi; Mustika, Haryanti; Kusumawardani, Sri Suning (Gadjah Mada Journal of Psychology (GamaJoP), 2024)
The use of online platforms in testing is a necessity nowadays, especially in an academic context. The platform used in UGM, namely eLOK, provides a testing facility which enable the lecturers to simultaneously see the results of the test evaluations and questions directly from the platform. However, there haven’t been any studies that compare the evaluation results using UGM’s eLOK with other approaches. Therefore, this study compared evaluation results from UGM’s eLOK with the Classical Test Theory (CTT) and Item Response Theory 2-Parameter Logistics (IRT 2-PL) approach using the Graded Response Model (GRM). This study included 22 active students who took the test using the UGM’s eLOK platform in the Multivariate Statistics course during the even semester of 2020/2021 academic year. The results of the analysis showed that the evaluation using the UGM’s eLOK platform had close equivalence with the CTT approach, although each parameter’s value was slightly different. In addition, the results of the IRT analysis were found to have far differences with the other two methods, but these results only slightly reflect the actual parameters due to the minimal number of subjects. The results of this study can be used as a reference in using UGM’s eLOK as a student academic testing platform, where lecturers are able to evaluate the quality of the tests and items given to test.